English Communication Competence through Extensive Reading - Dr. Vivek Mehrotra (International Journal of Advanced Science and Technology, 2020)
To become a full man one should read extensively. The competence of English Communication excels when one reads skillfully. This paper talks about the use of reading extensively and the techniques, methodologies, strategies and motivations executed by the teachers from school level to University level. Human life can significantly change if we have the habit of reading. It not only enriches our knowledge but also amuse us greatly. Every motor activity has some techniques to be followed to get the fruitful result. At the growing stage reading habit should be nurtured well for speedy and healthy growth.  When the techniques are planted in the minds of young readers, the growth can be watched and nurtured by the planter, the teacher.